The Marketization of Educational Institutions in Increasing Sales Value at Nahdlatul Ulama Vocational High School - Adi Wibowo; Mohamad Madum; Ita Nurmalasari; Daimah Daimah (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
SMK NU Purworejo is a vocational school with an Islamic background under the auspices of the Nahdlatul Ulama organization. Over the past few years, the school has experienced ups and downs in the number of new students. This study examines the marketing strategy of education at SMK NU Bener Purworejo. This research aimed to find out the marketing strategies and results of the SMK NU Bener Purworejo in recruiting new students. This research used a qualitative descriptive design. Research results showed that marketing strategies and results carried out by SMK NU Bener varied greatly, including visiting community leaders, advertising media through distributing brochures and installation of 'banners' at strategic locations, school sports competitions, word of mouth, and socializing with junior high school (MTs/SMP). However, the marketing results are still far from expectations. Therefore the school is necessary to rebrand educational marketing strategies relevant to the current era to achieve the expected targets and combine offline and online marketing strategies that align with the digital era.